Phylogenetic analysis and biogeography of Scolia (Hymenoptera, Scoliidae, Scoliinae): implications for the classification and origin of Scoliini - Fernandes Golfetti, Ivan [UNESP]; da Silva, Marjorie [UNESP]; Dos Santos, Eduardo Fernando [UNESP]; Noll, Fernando Barbosa [UNESP] (Wiley, 2025)
Scoliidae is a commonly found cosmopolitan family and currently one of the most neglected taxa within Hymenoptera. As expected, information on the members of this group is scarce and extremely outdated, especially when it comes to their phylogenetic relationships. The genus Scolia Fabricius, 1755 includes species that do not present diagnostic characters used to identify the other genera of Scoliini, and so it can be considered a “dumping ground group”. Seeking to better understand the evolutionary history and, consequently, the morphological variation in “New World” Scolia species, the phylogenetic relationships among all species from the Neotropical and Nearctic Regions and their biogeography are analysed for the first time. For this, 104 morphological characters are proposed from males and females of 45 species. The phylogenetic analysis points to the monophyly of the “New World” species, and the biogeographical analysis indicates that the “New World” species originated from a Palaearctic ancestor, through a dispersal event to the Nearctic Region. Considering the taxonomic history and phylogenetic relationships obtained, aiming to initially resolve a part of the chaotic taxonomic situation of Scolia and its subgenera, here we proposed that the subgenus Discolia should be restricted exclusively to the “New World” and the species from the “Old World” should no longer be treated as Discolia, being considered as members of Scolia s.s. Additionally, Hesperoscolia should be considered a junior synonym of Discolia. Furthermore, the phylogenetic analysis confirms the monophyly of most Scoliini genera included in it.